TRACES OF THE TIME WHICH REMAINS:: VIGNETTES ON THE ART AND TIME OF DYING - Wozniak, Jason Thomas (Revista Sul-Americana de Filosofia e Educação (RESAFE), 2015)
TRACES OF THE TIME WHICH REMAINS: VIGNETTES ON THE ART AND TIME OF DYING